ANALISIS PERMINTAAN PADA USAHA REKLAME DAN ADVERTISING DI KOTA PEKANBARU - Diny Oktariani; Syafril Basri; Eka Armas Pailis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to analyze the factors that influence the demand in business and advertising billboards in the city of Pekanbaru. Selection of the sample in this study using accidental sampling method, in order to obtain as many as 100 samples. The research method in this study using quantitative descriptive approach using multiple linear regression analysis. The dependent variable in this study is the demand on billboards and advertising efforts. And the independent variables in this study are the price of the product and income respondents. While the methods used in this research is multiple linear regression. Results of this study stated that the product price variable significant negative effect on demand in the business and advertising billboards. While the variable income respondents did not affect the demand in business and advertising billboards in the city of Pekanbaru. From the results and analysis of data, it could be concluded that the price has a dominant influence on the demand on billboards and advertising efforts. In accordance with the law of demand that is, the lower the price of an item then the more ppermintaan to such articles. Conversely, the higher the price of an item then makkin little demand for such goods. While there are other factors that can affect demand on billboards and advertising efforts that are not discussed in this study.Keywords: demand, price and revenue respoonden